GREEN INNOVATION AND SUSTAINABLE MANAGEMENT: STRATEGIES FOR LONG-TERM COMPETITIVE ADVANTAGE - Hardi Mulyono; Alistraja Dison Silalahi; Clarissa Tarigan (CV. Radja Publika, 2025)
This study explores the role of green innovation and sustainable management as integrated strategies for achieving long-term competitive advantage in modern business environments. As global awareness of environmental and social issues intensifies, organizations are increasingly pressured to adopt eco-friendly practices without compromising profitability. This paper analyzes how green innovation—through the development of sustainable products, cleaner production processes, and eco-conscious business models—serves as a catalyst for organizational resilience and market differentiation. Furthermore, it examines the strategic alignment of sustainability principles within corporate management systems, emphasizing stakeholder engagement, resource efficiency, and long-term value creation. Drawing on case studies and recent empirical findings, the research highlights key success factors, barriers to adoption, and the measurable impact of green innovation on firm performance. The findings suggest that firms that embed sustainability into their core strategies not only meet regulatory and ethical expectations but also unlock new growth opportunities and strengthen brand reputation. This paper contributes to the literature by presenting a comprehensive framework for integrating green innovation into sustainable management, positioning it as a vital lever for achieving sustained competitive advantage.